Picea mariana ((P. Mill.) B.P.S), P. abies (L.), Pinus contorta (Dougl.) och P. sylvestris (L.) - Dermer, Richard (2007)
Swedish forests are dominated by just two conifer species Norway spruce and Scotch pine. They are not able to achieve the highest possible production or fulfill industry demands for raw materials. The introduction of exotic conifers can potentially meet these shortcomings and present a relevant solution. This study was conducted in a block experiment with ten blocks planted in 1987 by SCA in North Sweden. The objective of the block experiment was to study if Black spruce is an appropriate alternative to Lodgepole pine, Norway spruce and Scotch pine on different site classes. Each block in experiment includes four planted treatments: One of each tree species, which lies parallel into each other in slopes. The basic data for this study were collected from three of the ten blocks which were all located in the province of Jämtland. The purpose of this study was to compare production, quality, damages and survival for Black spruce to Lodgepole pine, Norway spruce and Scots pine. The hypothesis was that the performance varies with site type. Site index was classified according to vegetation type. On average, after 19 growing seasons, Lodgepole pine had the highest dominant height and basal area. The survival for Lodgepole pine showed no significant difference between sites. However, the dominant height for Lodgepole pine generally increased with site index. The most frequently damages on the Lodgepole pine were spike knot and bend stems. Overall Scots pine performed second best in terms of production but it was the most damaged species and the most common damages on Scots pine were spike knots and pine twisting rust. The survival of Scots pine decreased with increasing site class. Also Black spruce and Norway spruce had the lowest survival on fertile sites. The dominant height for Black spruce was independent of the site index. Norway spruce had significantly higher dominant heights on the best site class compared to all other two site classes. According to this study, from a management point of view, Black spruce is ...